Performance Evaluation of Recycled Coarse Aggregate on Compressive Strength of Concrete - Malla, Tek Bahadur; Baniya, Arjun; Malla, Suresh; Paudel, Rabindra (Journal of Sustainability and Environmental Management, 2024)
The recycling of construction and demolition waste (CDW) is of paramount importance due to its sustainability and economic benefits, encompassing the reduction of landfill waste, conservation of natural resources, and mitigation of pollution. This practice has become integral to the construction industry, particularly in addressing the substantial construction waste generated from the demolition of reinforced concrete (RC) structures. The experimental examination of the performance of recycled coarse aggregate (RCA) on concrete behavior is fundamental in this context. Recycled Coarse Aggregate (RCA) is produced by crushing, screening, and salvaging concrete waste from demolished structures. A study was conducted to examine the properties of recycled coarse aggregate intended for use as coarse aggregate. The percentage of recycled coarse aggregate replacing natural coarse aggregate varied at 0%, 25%, 50%, 75%, and 100%. Concrete cubes were cast and tested in laboratory. To assess performance across various curing periods, 90 standard concrete cubes are formed as NCA alternatives, and their compressive strength is evaluated at 7, 14, and 28 days. After analyzing the physical and mechanical properties of these proportions, it was observed that, except for 75% and 100% replacements, all met the specified limits. The results of the compressive strength tests indicated that both M20 and M25 design mix concretes, without admixture and with 100% NCA, showed higher values at 27.05 MPa and 32.09 MPa, respectively. Conversely, 100% RCA recorded the lowest values at 18.93 MPa and 22.07 MPa for M20 and M25, respectively. The tests were conducted in accordance with the procedures outlined in the Standard IS Codes. The results show that up to 50% replacements of natural crushed aggregate have nominal strength of concrete. The analysis of coarse aggregate and concrete mix test results for the mentioned proportions suggests that up to 50% of natural crushed aggregate can be replaced by recycled coarse aggregate without compromising the characteristics strength of concrete.